2018
DOI: 10.1097/eja.0000000000000866
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone concentration affecting rocuronium-induced neuromuscular blockade and sugammadex reversal in a rat phrenic nerve-hemidiaphragm model

Abstract: Acute bolus administration of dexamethasone at clinical concentrations had no effect on NMB or on sugammadex reversal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Only a few in vitro or ex vivo studies exist regarding the interaction of rocuronium and sugammadex 2933 ; thus, there is no consensus on the recommended dose of sugammadex to be used in an ex vivo study. Previously, we have used an equimolar dose of sugammadex and rocuronium 30,33 ; this was based on the mechanism of action of sugammadex which encapsulates the free rocuronium molecules in 1: 1 molecular ratio 34 . However, in a clinical setting, a 0.6 mg kg −1 dose of rocuronium is routinely used, and 4 mg kg −1 dose of sugammadex is recommended by the manufacturer’s guideline when no twitch response on a TOF (and post-tetanic count ≥ 1) is seen.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few in vitro or ex vivo studies exist regarding the interaction of rocuronium and sugammadex 2933 ; thus, there is no consensus on the recommended dose of sugammadex to be used in an ex vivo study. Previously, we have used an equimolar dose of sugammadex and rocuronium 30,33 ; this was based on the mechanism of action of sugammadex which encapsulates the free rocuronium molecules in 1: 1 molecular ratio 34 . However, in a clinical setting, a 0.6 mg kg −1 dose of rocuronium is routinely used, and 4 mg kg −1 dose of sugammadex is recommended by the manufacturer’s guideline when no twitch response on a TOF (and post-tetanic count ≥ 1) is seen.…”
Section: Discussionmentioning
confidence: 99%
“…The application of intravenous perioperative methylprednisolone can also reduce the period of action of neuromuscular blockers 10 . Several trials on phrenic nerve‐diaphragm preparations in rats have also shown that dexamethasone curtails the period of action of neuromuscular blockers 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…10 Several trials on phrenic nerve-diaphragm preparations in rats have also shown that dexamethasone curtails the period of action of neuromuscular blockers. 11,12 The interest in a potential interaction of dexamethasone with neuromuscular blockade primarily came up after the introduction of sugammadex into clinical practice as it possesses a similar steroidal ring-like rocuronium with an initial in vitro 13 study. Soltész et al 14 were the first to demonstrate that a single dose of intravenous dexamethasone can attenuate the duration of action of rocuronium.…”
Section: Introductionmentioning
confidence: 99%